Sylepta sp. (Lepidoptera: Pyralidae) - a new pest of Soalu (Litsaea monopetala) in Kalimpong Hills (The Journal of Plant Protection Sciences, 2023)
Muga culture is an age-old practice in the  Brahmaputra valley of Assam. During the  year 2010, muga sericulture has been intro duced in Kalimpong hills (latitude 27°06′N,  longitude 88°47′E, 1247 m above msl) for pro duction of seed crop which is adversely af fected in Assam due to increase of tempera ture as a result of global warming. Soalu [Litsaea monopetala (Roxb) Pearson]  (Family: Lauraceae) is one of the primary  food plants of muga silkworm (Antheraea as samensis Helfer). It grows abundantly in the  hills of Kalimpong. Muga food plants are usu ally attacked by many pests like shoot borer,  trunk borer, leaf miners, leaf galls and mealy  bugs (1,2). Incidence of pest adversely affects  leaf yield and quality. During the year 2011, a  new pest infestation caused by leaf roller was  found severely affected foliage of soalu plants  in a place (2702'35''N/88027'57"E) of Kalim pong Hills. The aim of this paper is to high light important observations of the new pest  affected the Soalu food plant of muga silk worm in the Kalimpong hills. Pest damage  symptoms, larval, pupal character and adult  stage were photographed by Kodak AF  3X10.3 mega pixels camera. For identifica tion of the pest, adult moths were dried in  oven and kept in glass vials and despatched to  the Zoological Survey of India, Central Ento mological Laboratory Kolkata (India) for  identification. It was observed that leaf roller  incidence appeared on 2nd week of July and  continued up to September. Caterpillars at tacked the top leaf of the branch and formed a  protective shelter of leaves that they rolled  and web together with silken thread (Fig. 1a).  Caterpillar feed rolled leaves from the margin.  In each rolled leaves, 4-6 nos
Keywords: abdominal prolegs; Lauraceae; Brahmaputra valley